Parameter estimation of harmonics arising in electrical instruments of smart grids using cuckoo search heuristics - Malik, Naveed Ahmed; Chang, Ching-Lung; Chaudhary, Naveed Ishtiaq; Khan, Zeshan Aslam; Zahoor Raja, Muhammad Asif; Kiani, Adiqa Kausar; Milyani, Ahmed H.; Azhari, Abdullah Ahmed (Frontiers in Energy Research, 2022)
The accurate estimation of power signal parameters allows smart grids to optimize power delivery efficiency, improve equipment utilization, and control power flow among generation nodes and loads. However, practically it becomes a challenging task because of the presence of harmonic distortions. In this study, a parameter estimation of the power system harmonics is investigated through swarm intelligence–based optimization strength of the cuckoo search algorithm. The performance evaluation is conducted in detail for different generations and particle sizes and for different signal-to-noise ratios. The simulation results reveal that the cuckoo search optimization heuristic accurately estimates the amplitude and phase parameters of the power system harmonics and is robust against different signal-to-noise ratios.